Nanyang Technological University indoor map - Ang, Benjamin Wei Ming (Nanyang Technological University, 2021)
This is a continuation work of an indoor map created by Graduate T. Chung Lok for the Final Year Project for AY20/21. The indoor map was created with the intention to aid students, staff and potential visitors in searching for rooms and facilities as well as navigating around the campus. Since the completion of this indoor map, Nanyang Technological University has launched its own interactive indoor map, like this project. A review is done to discuss on the pros and cons of the official indoor map and use it as a potential guideline to guide the improvement work on the created indoor map. This continuation work on the indoor map has extended out the area of coverage to new buildings to allow users to navigate more areas. Additional work such as scraping of faculty information, adding staff allocation to the staff rooms and live webcam view of various areas were done to provide more features and information for users. As the indoor map is still incomplete, further improvement works can be done. Increasing the area of coverage together with additional features like indoor positioning, transition to mobile platform as well as mode of travel are some extension examples for future works.